The effect of silver crucian carp (Carassius auratus gibelio Bloch) on the yields and the production value of common carp (Cyprius carpio) fingerlings - Bársony, Péter; Pócsi, László; Szabó, András (Acta Agraria Debreceniensis, 2006)
During the last few years, the spread of the silver crucian carp has caused significant problems in pond fish culture. One of the main challenges of successful fish production in fishponds, is to rid ponds of the silver crucian carp. The nature of the damage caused by silver crucian carp is a complex question. To get into the ponds, the crucian carps occupy the territory before the common carp, and competes for food with common carp. The silver crucian carp has a less favorable food coefficient than the common carp, and it’s value is also lower. Therefore, the income of the fish farm decreases. In the course of the experiment, carp fry were stocked in 5 nursing ponds at the same stocking rate, with different (0,- 50-, 100-, 150-, 200%) stocking rates of silver crucian carp fry, respectively. At the end of the experiment, the yield/hectar and the production values were calculated. The experiment proved that the presence of the silver crucian carp in the fishponds causes lower yields and production values.